Investing in the stock market: The long-term view matters - Markus Demary (Institut der deutschen Wirtschaft (IW), 2017)
After the internet bubble collapsed in 2000, German households have reduced their investments in the stock market. Losses at that time were not so much caused by market volatility, but the consequence of short-term speculation. However, putting savings into the stock market can be very profitable for households, when the investment horizon is sufficiently long.
Keywords: 330